Epoxidized graphene grid for highly efficient high-resolution cryoEM structural analysis - Junso Fujita; Fumiaki Makino; Haruyasu Asahara; Maiko Moriguchi; Shota Kumano; Itsuki Anzai; Jun-ichi Kishikawa; Yoshiharu Matsuura; Takayuki Kato; Keiichi Namba; Tsuyoshi Inoue (Scientific Reports, 2023)
Abstract Functionalization of graphene is one of the most important fundamental technologies in a wide variety of fields including industry and biochemistry. We have successfully achieved a novel oxidative modification of graphene using photoactivated ClO2 · as a mild oxidant and confirmed the oxidized graphene grid is storable with its functionality for at least three months under N2 atmosphere. Subsequent chemical functionalization enabled us to develop an epoxidized graphene grid (EG-grid™), which effectively adsorbs protein particles for electron cryomicroscopy (cryoEM) image analysis. The EG-grid dramatically improved the particle density and orientation distribution. The density maps of GroEL and glyceraldehyde 3-phosphate dehydrogenase (GAPDH) were reconstructed at 1.99 and 2.16 Å resolution from only 504 and 241 micrographs, respectively. A sample solution of 0.1 mg ml−1 was sufficient to reconstruct a 3.10 Å resolution map of SARS-CoV-2 spike protein from 1163 micrographs. The map resolutions of β-galactosidase and apoferritin easily reached 1.81 Å and 1.29 Å resolution, respectively, indicating its atomic-resolution imaging capability. Thus, the EG-grid will be an extremely powerful tool for highly efficient high-resolution cryoEM structural analysis of biological macromolecules.